PENERAPAN ARSITEKTUR ORGANIK PADA KAWASAN AGROWISATA BUAH DI PABUARAN, KABUPATEN SERANG - Erlis Tika Yuli Setyani; Dody Kurniawan; Tri Endangsih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Plantation is one of the largest natural potentials in Indonesia, which has a tropical climate. Economic activities based on food crops and horticulture are very important (strategic) activities in Indonesia. In terms of potential, the availability of land and natural resources is very large. So that with the design of this Fruit Agrotourism Area, it is hoped that later it will be able to accommodate tourism management and plantation development, especially for the Pabuaran area, Serang Regency. With the application of the concept of organic architecture that is able to adapt to the conditions around the Pabuaran area to support the function of the building and comfort for users.